Storage method of biological tissue material
By hydrogel coating treatment on biological tissue materials, the problems of aldehyde group residues and calcification caused by glutaraldehyde solution storage are solved, the effect of avoiding dehydration damage is achieved, and storage stability and mechanical properties are improved.
Patent Information
- Application Number
- CN202311235733.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-28
AI Technical Summary
When biotissue materials are stored in glutaraldehyde solution, they can cause problems with aldehyde group residues and calcification, while dry storage may cause permanent damage and mechanical properties.
The hydrogel coating treatment method is used to form a hydrogel coating by self-assembly layer by layer to avoid direct contact between biological tissue materials and glutaraldehyde, and no dehydration treatment is required.
It effectively avoids the problems of aldehyde residue and calcification, maintains the anti-calcification ability and mechanical properties of biological tissue materials, and improves storage stability.
Smart Images

Figure CN119699315A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials, and relates to a method for processing biological tissue materials, and in particular to a method for storing biological tissue materials. Background Art
[0002] In order to maintain the performance of biological tissue materials, they often need to be stored in a liquid environment. Once out of the liquid environment, irreversible structural and performance damage will be caused to the biological tissue materials. Taking biological valve materials as an example, biological valve materials are generally stored in low-concentration glutaraldehyde solutions, which provide a relatively safe and effective sterile wet environment for the long-term preservation of biological valve materials. However, long-term contact of glutaraldehyde solution with biological valve materials will cause a large number of free aldehyde groups to remain on the surface of the biological valve materials, which is not conducive to maintaining the anti-calcification ability of biological valve materials.
[0003] Based on the disadvantages of wet storage of glutaraldehyde solution, those skilled in the art have proposed the concept of dry storage, which can avoid the problem of residual aldehyde groups caused by glutaraldehyde storage.
[0004] However, the dry storage method requires the use of alcoholic organic solvents for dehydration, which inevitably causes permanent damage to biological tissue materials and affects the mechanical properties of the valve. In addition, the antibacterial advantage of non-glutaraldehyde storage is not obvious. Although glutaraldehyde storage will bring about the problem of aldehyde residues, glutaraldehyde storage has a good antibacterial advantage.
[0005] Therefore, it is necessary to provide a storage method for biological tissue materials that can effectively avoid aldehyde residues and utilize the excellent antibacterial function of glutaraldehyde. Summary of the invention
[0006] The object of the present invention is to provide a storage method for biological tissue materials, which can overcome the storage defects of glutaraldehyde and give full play to the antibacterial advantages of glutaraldehyde; moreover, it can also avoid the problems of too low water content in dry storage of biological tissue materials, which leads to the attenuation of long-term storage performance of biological tissue materials and difficulty in rehydration.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] The present invention provides a storage method for biological tissue materials, the storage method comprising:
[0009] The biological tissue material is subjected to hydrogel coating treatment to form a hydrogel coating by layer-by-layer self-assembly.
[0010] Direct preservation of biological tissue materials with glutaraldehyde will reduce the anti-calcification ability due to glutaraldehyde residue. The present invention performs hydrogel coating treatment on biological tissue materials to form a hydrogel coating that prevents direct contact between biological tissue materials and glutaraldehyde, effectively avoiding the problems of aldehyde residue and calcification caused by glutaraldehyde solution preservation; moreover, the storage method provided by the present invention does not require dehydration treatment, which can avoid the problems of too low water content in dry-preserved biological tissue materials, resulting in storage performance attenuation and difficulty in rehydration; in addition, the hydrogel coating formed by the hydrogel coating treatment can also make the surface of the biological tissue material have a water-retaining effect, thereby improving the storage stability.
[0011] In view of the different storage requirements of different biological tissue materials, the thickness of the formed hydrogel coating can be flexibly controlled by the layer-by-layer self-assembly method, and the thickness of the obtained hydrogel coating is uniform; moreover, the layer-by-layer self-assembly method is simple, has low requirements on equipment, and the strength of the prepared hydrogel coating is high, which is convenient for the stable storage of biological tissue materials. Therefore, as a preferred technical solution, the method for forming the hydrogel coating includes layer-by-layer self-assembly.
[0012] Preferably, the hydrogel coating treatment comprises: extracting the biological tissue material in a material preservation solution at least once, and performing light induction at least once each time of extraction to form a hydrogel coating that protects the biological tissue material.
[0013] Preferably, the soaking time of each extraction is 2-8 min, for example, 2 min, 4 min, 5 min, 6 min or 8 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] Preferably, the number of layers of the hydrogel coating formed by the layer-by-layer self-assembly is 3-10 layers, for example, 3 layers, 5 layers, 6 layers, 8 layers or 10 layers, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] In the present invention, the number of layers of the hydrogel coating is related to the number of light inductions after extraction, and one layer of the hydrogel coating is formed each time the light is induced.
[0016] Preferably, the material preservation solution contains 0.01-1% (w / w) of photoinitiator and 0.01-0.2% (w / w) of double-bond modified polymer material.
[0017] The material preservation solution of the present invention contains 0.01-1% (w / w) photoinitiator, for example, it can be 0.01% (w / w), 0.1% (w / w), 0.3% (w / w), 0.5% (w / w), 0.6% (w / w), 0.8% (w / w) or 1% (w / w), but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] The present invention achieves the regulation of cross-linking efficiency by controlling the content of the photoinitiator in the material preservation solution, avoids the problem of too fast or too slow cross-linking rate, and improves the uniformity of cross-linking.
[0019] The material preservation solution of the present invention contains 0.01-0.2% (w / w) double-bond modified polymer material, for example, it can be 0.01% (w / w), 0.05% (w / w), 0.1% (w / w), 0.15% (w / w) or 0.2% (w / w), but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Preferably, the photoinitiator comprises an ultraviolet photoinitiator.
[0021] Preferably, the ultraviolet light initiator includes any one of 2-hydroxy-2-methylphenylacetone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylphenylacetone, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone or 2-hydroxy-2-methyl-1-[4-(tert-butyl)phenyl]-1-propanone or a combination of at least two thereof. A typical but non-limiting combination includes 2-hydroxy-2-methylphenylacetone and 2-hydroxy-4-(2-hydroxyethoxy)-2-methylphenylacetone. 1-[4-(tert-butyl)phenyl]-1-propanone, or a combination of 2-hydroxy-2-methylphenylpropanone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylphenylpropanone, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone and 2-hydroxy-2-methyl-1-[4-(tert-butyl)phenyl]-1-propanone.
[0022] Preferably, the double-bond modified polymer material includes any one or a combination of at least two of chitosan, chitosan derivatives, gelatin, gelatin derivatives, soluble cellulose, soluble cellulose derivatives, sodium alginate, sodium alginate derivatives, hyaluronic acid, hyaluronic acid derivatives, chondroitin sulfate, chondroitin sulfate derivatives, silk protein, silk protein derivatives, β-cyclodextrin or β-cyclodextrin derivatives, preferably chitosan and / or chitosan derivatives.
[0023] The present invention selects a suitable double-bond modified polymer material and forms an interpenetrating network structure by inducing double bonds to form photo-crosslinkable free radicals.
[0024] Preferably, the material preservation solution also contains 0.01-1mM of antibacterial active substances, for example, it can be 0.01mM, 0.1mM, 0.3mM, 0.5mM, 0.8mM or 1mM, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] The present invention can improve the antibacterial performance of the hydrogel coating and improve the problem of bacterial contamination during long-term storage by adding antibacterial active substances into the material preservation solution.
[0026] Preferably, the antibacterial active substance includes any one of biguanides, isothiazoles, phenol ethers or phenols, or a combination of at least two of them. Typical but non-limiting combinations include a combination of biguanides and isothiazoles, a combination of phenol ethers and phenols, or a combination of biguanides, isothiazoles, phenol ethers and phenols.
[0027] Preferably, the temperature of the hydrogel coating treatment is 25-37°C, for example, 25°C, 27°C, 28°C, 30°C, 32°C, 35°C or 37°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the biological tissue material includes any one of pericardial tissue, cartilage tissue or skin tissue.
[0029] The pericardial tissue of the present invention includes, but is not limited to, any one of the aortic valve, mitral valve, tricuspid valve, pulmonary artery, surgical valve or venous valve, or a combination of at least two thereof.
[0030] Preferably, the biological tissue material is surface treated before being treated with the hydrogel coating.
[0031] The surface treatment technology adopted in the preservation method provided by the present invention improves the structural stability of the obtained hydrogel coating, so that the contact between glutaraldehyde and the biological tissue material can be avoided even after the biological tissue material is preserved for a long time.
[0032] Preferably, the surface treatment includes any one of pre-crosslinking treatment, surface modification treatment or staggered crosslinking treatment or a combination of at least two thereof. Typical but non-limiting combinations include a combination of pre-crosslinking treatment and surface modification treatment, a combination of surface modification treatment and staggered crosslinking treatment, a combination of pre-crosslinking treatment and staggered crosslinking treatment, or a combination of pre-crosslinking treatment, surface modification treatment and staggered crosslinking treatment.
[0033] Preferably, the surface modification treatment includes any one of oxidation treatment, grafting treatment or reduction treatment, or a combination of at least two of them.
[0034] The surface modification treatment of the present invention can not only improve the anti-calcification performance of the biological tissue material, but also improve the structural stability of the obtained hydrogel coating.
[0035] The present invention is beneficial to shaping the biological tissue material by performing pre-crosslinking treatment.
[0036] Preferably, the pre-crosslinking treatment comprises: soaking in a glutaraldehyde solution.
[0037] Preferably, the concentration of the glutaraldehyde solution is 0.1-0.5% (w / w), for example, it can be 0.1% (w / w), 0.2% (w / w), 0.3% (w / w), 0.4% (w / w) or 0.5% (w / w), but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, the pre-crosslinking treatment is carried out at a temperature of 25-37° C. and for a time of 10-60 min.
[0039] The temperature of the pre-crosslinking treatment of the present invention is 25-37°C, for example, it can be 25°C, 27°C, 28°C, 30°C, 32°C, 35°C or 37°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] The time of the pre-crosslinking treatment of the present invention is 10-60 minutes, for example, it can be 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes or 60 minutes, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0041] The oxidation treatment of the present invention is beneficial to improving the bio-tissue compatibility of the bio-tissue material.
[0042] Preferably, the oxidation treatment comprises: immersing in an oxidant solution.
[0043] Preferably, the concentration of the oxidant solution is 0.01-0.1 mM, for example, 0.01 mM, 0.03 mM, 0.05 mM, 0.08 mM or 0.1 mM, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0044] Preferably, the oxidant in the oxidant solution comprises any one of sodium periodate, potassium periodate, potassium dichromate, peracetic acid, hydrogen peroxide or 2,2,6,6-tetramethylpiperidinium oxide, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of sodium periodate and potassium periodate, a combination of potassium dichromate and peracetic acid, a combination of hydrogen peroxide and 2,2,6,6-tetramethylpiperidinium oxide, a combination of sodium periodate, potassium periodate and potassium dichromate, a combination of potassium dichromate, peracetic acid and hydrogen peroxide, or a combination of sodium periodate, potassium periodate, potassium dichromate, peracetic acid, hydrogen peroxide and 2,2,6,6-tetramethylpiperidinium oxide.
[0045] Preferably, the oxidation treatment is carried out at a temperature of 25-37°C and for a time of 10-50 minutes.
[0046] The temperature of the oxidation treatment of the present invention is 25-37°C, for example, it can be 25°C, 27°C, 28°C, 30°C, 32°C, 35°C or 37°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] The time of the oxidation treatment in the present invention is 10-50 minutes, for example, it can be 10 minutes, 20 minutes, 30 minutes, 40 minutes or 50 minutes, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0048] The grafting treatment of the present invention is beneficial to improving the stability of the hydrogel coating and maintaining the performance of the biological tissue material.
[0049] Preferably, the grafting treatment comprises: immersing in a solution containing a terminal active double bond structure substance.
[0050] Preferably, the concentration of the solution containing the terminal active double bond structure substance is 0.01-0.1M, for example, it can be 0.01M, 0.03M, 0.05M, 0.06M, 0.08M or 0.1M, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] Preferably, the terminal active double bond structure-containing substance comprises any one of methacrylic anhydride, methacrylic anhydride oil, di(2-methyl-2-acrylic acid) 2-hydroxy-1,3-propylene glycol ester, hydroxyethyl methacrylate or acryloyl chloride, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of methacrylic anhydride and methacrylic anhydride oil, a combination of di(2-methyl-2-acrylic acid) 2-hydroxy-1,3-propylene glycol ester and hydroxyethyl methacrylate, a combination of hydroxyethyl methacrylate and acryloyl chloride, a combination of methacrylic anhydride, methacrylic anhydride oil and di(2-methyl-2-acrylic acid) 2-hydroxy-1,3-propylene glycol ester, a combination of di(2-methyl-2-acrylic acid) 2-hydroxy-1,3-propylene glycol ester, hydroxyethyl methacrylate and acryloyl chloride, or a combination of methacrylic anhydride, methacrylic anhydride oil, di(2-methyl-2-acrylic acid) 2-hydroxy-1,3-propylene glycol ester, hydroxyethyl methacrylate and acryloyl chloride.
[0052] Preferably, the grafting treatment is carried out at a temperature of 25-37° C. and for a time of 12-24 hours.
[0053] The temperature of the grafting treatment of the present invention is 25-37°C, for example, it can be 25°C, 27°C, 28°C, 30°C, 32°C, 35°C or 37°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] The grafting treatment time of the present invention is 12-24 hours, for example, it can be 12 hours, 15 hours, 16 hours, 18 hours, 20 hours, 21 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] The reduction treatment of the present invention is beneficial to improving the anti-calcification performance of biological tissue materials.
[0056] Preferably, the reduction treatment comprises: immersing in a reducing agent solution.
[0057] Preferably, the concentration of the reducing agent solution is 0.01-0.1M, for example, 0.01M, 0.03M, 0.05M, 0.06M, 0.08M or 0.1M, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0058] Preferably, the reducing agent in the reducing agent solution includes any one of sodium borohydride, sodium cyanoborohydride or sodium triacetylborohydride, or a combination of at least two of them. Typical but non-limiting combinations include a combination of sodium borohydride and sodium cyanoborohydride, a combination of sodium cyanoborohydride and sodium triacetylborohydride, a combination of sodium borohydride and sodium triacetylborohydride, or a combination of sodium borohydride, sodium cyanoborohydride and sodium triacetylborohydride.
[0059] Preferably, the reduction treatment is carried out at a temperature of 25-37° C. and for a time of 12-24 h.
[0060] The temperature of the reduction treatment of the present invention is 25-37°C, for example, it can be 25°C, 27°C, 28°C, 30°C, 32°C, 35°C or 37°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] The time of the reduction treatment in the present invention is 12-24 hours, for example, it can be 12 hours, 15 hours, 16 hours, 18 hours, 20 hours, 21 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] The solution environment of the surface modification treatment of the present invention is a buffer solution system and / or an organic solvent system. The buffer of the buffer solution system includes any one of MES buffer, HEPES buffer, PBS buffer or CB buffer or a combination of at least two. Typical but non-limiting combinations include a combination of MES buffer and HEPES buffer, a combination of PBS buffer and CB buffer, a combination of HEPES, PBS buffer and CB buffer, or a combination of MES buffer, HEPES buffer, PBS buffer and CB buffer.
[0063] The dislocation cross-linking treatment of the present invention forms a network structure through cross-linking of molecular chains, thereby improving the degradation resistance of the biological tissue material and maintaining the performance of the biological tissue material after long-term storage.
[0064] Preferably, the staggered cross-linking treatment includes a first cross-linking and a second cross-linking performed sequentially.
[0065] Preferably, the first cross-linking comprises: immersing in a mixed solution of a carbonyl activation reagent and a coupling reagent.
[0066] Preferably, the concentration of the carbonyl activation reagent in the mixed solution is 20-80 mM, and the concentration of the coupling reagent is 10-40 mM.
[0067] The concentration of the carbonyl activating agent in the mixed solution of the present invention is 20-80 mM, for example, 20 mM, 30 mM, 40 mM, 50 mM, 60 mM, 70 mM or 80 mM, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] The concentration of the coupling reagent in the mixed solution of the present invention is 10-40mM, for example, it can be 10mM, 15mM, 20mM, 25mM, 30mM, 35mM or 40mM, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] Preferably, the carbonyl activating agent comprises any one of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride or dimethylaminopropyl ethylcarboamide, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, a combination of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and dimethylaminopropyl ethylcarboamide, or a combination of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and dimethylaminopropyl ethylcarboamide.
[0070] Preferably, the coupling reagent includes any one of N-hydroxysuccinimide sulfonic acid sodium salt, 1-hydroxybenzotriazole or benzyloxycarbonyl succinimide or a combination of at least two thereof. Typical but non-limiting combinations include a combination of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide sulfonic acid sodium salt, a combination of 1-hydroxybenzotriazole and benzyloxycarbonyl succinimide, or a combination of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide sulfonic acid sodium salt, 1-hydroxybenzotriazole and benzyloxycarbonyl succinimide.
[0071] Preferably, the temperature of the first cross-linking is 25-37° C. and the time is 4-12 h.
[0072] The first cross-linking temperature of the present invention is 25-37°C, for example, it can be 25°C, 27°C, 28°C, 30°C, 32°C, 35°C or 37°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0073] The first cross-linking time of the present invention is 4-12 hours, for example, 4 hours, 5 hours, 6 hours, 8 hours, 10 hours or 12 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0074] Preferably, the second cross-linking comprises: immersing in a metal inhibitor solution.
[0075] Preferably, the metal ion concentration in the metal inhibitor solution is 1-10 mM, for example, 1 mM, 3 mM, 5 mM, 8 mM or 10 mM, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0076] Preferably, the metal ions in the metal inhibitor solution include any one of iron ions, zinc ions or magnesium ions, or a combination of at least two of them. Typical but non-limiting combinations include a combination of iron ions and zinc ions, a combination of zinc ions and magnesium ions, a combination of iron ions and magnesium ions, or a combination of iron ions, zinc ions and magnesium ions.
[0077] Preferably, the temperature of the second cross-linking is 5-15° C. and the time is 2-6 hours.
[0078] The temperature of the second crosslinking of the present invention is 5-15°C, for example, 5°C, 6°C, 7°C, 10°C, 12°C or 15°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0079] The second cross-linking time of the present invention is 2-6 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0080] Preferably, the storage method further comprises a decellularization treatment before the surface treatment.
[0081] Decellularization is beneficial to reduce the residual cellular components of biological tissue materials and reduce immune exclusion reactions; in addition, decellularization is also beneficial to reduce the phospholipid components of biological tissue materials, thereby reducing the deposition sites of calcium ions and improving the anti-calcification properties of biological tissue materials.
[0082] Preferably, the decellularization treatment comprises: soaking in a detergent solution.
[0083] Preferably, the decellularization treatment is carried out at a temperature of 5-15°C and for a time of 1-4 hours.
[0084] The temperature of the decellularization treatment of the present invention is 5-15°C, for example, it can be 5°C, 6°C, 8°C, 10°C, 12°C or 15°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0085] The time of the decellularization treatment of the present invention is 1-4 hours, for example, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0086] Preferably, the concentration of the detergent solution is 0.01-2% (w / w), for example, it can be 0.01% (w / w), 0.1% (w / w), 0.5% (w / w), 0.8% (w / w), 1% (w / w), 1.2% (w / w), 1.5% (w / w), 1.8% (w / w) or 2% (w / w), but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0087] Preferably, the detergent in the detergent solution includes any one of sodium dodecyl sulfate, hexadecyl ammonium bromide, a betaine-type detergent or Triton X-100, or a combination of at least two of them. Typical but non-limiting combinations include a combination of sodium dodecyl sulfate and hexadecyl ammonium bromide, a combination of a betaine-type detergent and Triton X-100, a combination of sodium dodecyl sulfate, a betaine-type detergent and Triton X-100, or a combination of sodium dodecyl sulfate, hexadecyl ammonium bromide, a betaine-type detergent and Triton X-100.
[0088] Preferably, the betaine-type detergent comprises 3-[N,N-dimethyldimethyl(3-myristoylamidepropyl)ammonium]propane-1-sulfonate (ABS-14) and / or 3-[N,N-dimethyl(3-palmitamidopropyl)ammonium]-propanesulfonic acid inner salt (ABS-16).
[0089] The purpose of the decellularization treatment of the present invention is to reduce the residual cell components. The present invention does not impose too many restrictions on the number of decellularization treatments. Exemplarily, the number of decellularization treatments is at least 1 time, for example, 1 time, 2 times or 3 times, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0090] As a preferred technical solution of the storage method of the present invention, the storage method comprises the following steps:
[0091] (1) The biological tissue material is immersed in a detergent solution with a concentration of 0.01-2% (w / w) at 5-15° C. for 1-4 hours to perform a decellularization treatment; the detergent in the detergent solution includes any one of sodium dodecyl sulfate, hexadecyl ammonium bromide, betaine-type detergent or Triton X-100, or a combination of at least two thereof;
[0092] (2) then immersing in a 0.1-0.5% (w / w) glutaraldehyde solution at 25-37° C. for 10-60 min to perform a pre-crosslinking treatment;
[0093] (3) then immersing in an oxidant solution with a concentration of 0.01-0.1 mM at 25-37° C. for 10-50 min for oxidation treatment; the oxidant in the oxidant solution comprises any one of sodium periodate, potassium periodate, potassium dichromate, peracetic acid, hydrogen peroxide or 2,2,6,6-tetramethylpiperidinyl oxide, or a combination of at least two thereof;
[0094] (4) then immersing in a solution containing a terminal active double bond structure substance at a concentration of 0.01-0.1 M at 25-37° C. for 12-24 hours for grafting treatment; the terminal active double bond structure substance comprises any one of methacrylic anhydride, methacrylic anhydride oil, di(2-methyl-2-acrylate) 2-hydroxy-1,3-propylene glycol ester, hydroxyethyl methacrylate or acryloyl chloride, or a combination of at least two thereof;
[0095] (5) then immersing in a reducing agent solution with a concentration of 0.01-0.1 M at 25-37° C. for 12-24 hours for reduction treatment; the reducing agent in the reducing agent solution includes any one of sodium borohydride, sodium cyanoborohydride or sodium triacetylborohydride, or a combination of at least two thereof;
[0096] (6) then sequentially performing a first crosslinking and a second crosslinking to perform a staggered crosslinking treatment;
[0097] The first cross-linking comprises: immersing in a mixed solution of a carbonyl activation reagent and a coupling reagent at 25-37° C. for 4-12 hours; the concentration of the carbonyl activation reagent in the mixed solution is 20-80 mM, and the concentration of the coupling reagent is 10-40 mM;
[0098] The second cross-linking comprises: immersing in a metal inhibitor solution having a metal ion concentration of 1-10 mM at 5-15° C.; the metal ions in the metal inhibitor solution include any one of iron ions, zinc ions or magnesium ions or a combination of at least two thereof;
[0099] (7) Finally, the material is extracted at least once in a material preservation solution at 25-37°C, and light induction is performed at least once each time the extraction is performed to form 3-10 layers of hydrogel coatings to protect the biological tissue material; the material preservation solution contains 0.01-1% (w / w) of a photoinitiator, 0.01-0.2% (w / w) of a double-bond modified polymer material, and 0.01-1 mM of an antibacterial active substance.
[0100] Compared with the prior art, the present invention has the following beneficial effects:
[0101] The present invention performs hydrogel coating treatment on biological tissue materials to form a hydrogel coating that prevents direct contact between biological tissue and glutaraldehyde, effectively avoiding problems such as aldehyde residue and calcification caused by storage in glutaraldehyde solution; moreover, the storage method provided by the present invention does not require dehydration treatment, and can avoid problems such as too low water content in dry-preserved biological tissue materials, resulting in storage performance attenuation and difficulty in rehydration; in addition, the hydrogel coating formed by the hydrogel coating treatment can also make the surface of the biological tissue material have a water-retaining effect, thereby improving storage stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0102] Figure 1 Schematic diagram of the surface chemical bond changes of biological tissue materials in Examples 9-15 of the present invention;
[0103] Figure 2-1 to Figure 2-3 This is a schematic diagram of the rehydration of the biological tissue material obtained after treatment in Example 5;
[0104] Figure 3-1 to Figure 3-3 This is a schematic diagram of the rehydration of the biological tissue material obtained after treatment in Example 7;
[0105] Figure 4-1 to Figure 4-3 This is a schematic diagram of the rehydration of the biological tissue material obtained after treatment in Example 12;
[0106] Figure 5-1 and Figure 5-2 Schematic diagram of the rehydration of biological tissue materials after natural dry storage.
[0107] Among them: S001 is a pre-crosslinking treatment; S002 is an oxidation treatment; S003 is a grafting treatment; S004 is a reduction treatment; S005 is a dislocation crosslinking treatment. DETAILED DESCRIPTION
[0108] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0109] In order to clearly illustrate the technical solution of the present invention, the biological tissue material in the specific implementation manner of the present invention is bovine pericardial tissue, and the composition of the biological tissue material should not be regarded as a specific limitation on the biological tissue material.
[0110] Example 1
[0111] This embodiment provides a storage method for biological tissue materials, the storage method comprising:
[0112] The biological tissue material was immersed in the material preservation solution at 30°C for 5 times of leaching, and light induction was performed each time of leaching to form 5 layers of hydrogel coating through layer-by-layer self-assembly;
[0113] The soaking time for each extraction was 5 min;
[0114] The material preservation solution contains 0.02% (w / w) 2-hydroxy-2-methylphenylacetone, 0.05% (w / w) carboxymethyl chitosan (substitution degree 80%) and 0.08 mM polyhexamethylene biguanide hydrochloride (XW3228958003).
[0115] Example 2
[0116] This embodiment provides a storage method for biological tissue materials, the storage method comprising:
[0117] The biological tissue material was immersed in the material preservation solution at 30°C for 10 extractions, and light induction was performed each time to form 10 layers of hydrogel coatings through layer-by-layer self-assembly.
[0118] The soaking time for each extraction was 2 min;
[0119] The material preservation solution contains 0.01% (w / w) 2-hydroxy-2-methylphenylacetone, 0.01% (w / w) carboxymethyl chitosan (substitution degree 80%) and 0.01 mM polyhexamethylene biguanide hydrochloride (XW3228958003).
[0120] Example 3
[0121] This embodiment provides a storage method for biological tissue materials, the storage method comprising:
[0122] The biological tissue material was immersed in the material preservation solution at 30°C for 3 times of leaching, and light induction was performed each time of leaching to form 3 layers of hydrogel coating through layer-by-layer self-assembly;
[0123] The soaking time for each extraction was 8 min;
[0124] The material preservation solution contains 1% (w / w) 2-hydroxy-2-methylphenylacetone, 0.2% (w / w) carboxymethyl chitosan (substitution degree 80%) and 1 mM polyhexamethylene biguanide hydrochloride (XW3228958003).
[0125] Example 4
[0126] This embodiment provides a storage method for biological tissue materials. Compared with embodiment 1, this embodiment further performs oxidation treatment before hydrogel coating treatment.
[0127] The oxidation treatment is: immersing in 0.1 mM potassium dichromate at 25° C. for 40 minutes.
[0128] Example 5
[0129] This embodiment provides a storage method for biological tissue materials. Compared with embodiment 1, this embodiment further performs a reduction treatment before the hydrogel coating treatment.
[0130] The reduction treatment is as follows: immersing in a PBS buffer solution containing 0.1 M sodium cyanoborohydride at 25° C. for 24 hours.
[0131] Example 6
[0132] This embodiment provides a method for storing biological tissue materials. Compared with embodiment 1, this embodiment further includes a grafting process before the hydrogel coating process.
[0133] The grafting treatment is as follows: immersing in a CB buffer solution containing 0.1 M hydroxyethyl methacrylate at 25° C. for 24 hours.
[0134] Example 7
[0135] This embodiment provides a method for storing biological tissue materials. Compared with embodiment 1, this embodiment further includes a pre-crosslinking treatment, a grafting treatment and a dislocation crosslinking treatment performed in sequence before the hydrogel coating treatment.
[0136] The pre-crosslinking treatment is: immersing in a 0.5% (w / w) glutaraldehyde solution at 37° C. for 20 minutes;
[0137] The grafting treatment is as follows: immersing in a CB buffer solution with a concentration of 0.1 M hydroxyethyl methacrylate at 25° C. for 24 hours;
[0138] The dislocation cross-linking treatment includes sequentially performing a first cross-linking and a second cross-linking;
[0139] The first cross-linking comprises: immersing in a mixed solution of a carbonyl activation reagent and a coupling reagent at 25° C. for 8 hours; the concentration of the carbonyl activation reagent in the mixed solution is 40 mM, and the concentration of the coupling reagent is 20 mM; the carbonyl activation reagent is 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride; and the coupling reagent is N-hydroxysuccinimide sulfonic acid sodium salt;
[0140] The second cross-linking comprises: immersing in a metal inhibitor solution with a magnesium concentration of 10 mM at 10° C. for 2 hours.
[0141] Example 8
[0142] This embodiment provides a method for storing biological tissue materials. Compared with Embodiment 7, this embodiment further includes a decellularization process before the pre-crosslinking process;
[0143] The decellularization treatment is as follows: the biological tissue material is immersed in 0.01% (w / w) sodium dodecyl sulfate at 10°C for 1 hour, and then rinsed with PBS buffer; then immersed in 0.5% (w / w) Triton X-100 at 10°C for 2 hours, and then rinsed with D-Hanks solution.
[0144] Example 9
[0145] The present invention provides a storage method for biological tissue materials, the storage method comprising: sequentially performing decellularization treatment, pre-crosslinking treatment, surface modification treatment, dislocation crosslinking treatment and hydrogel coating treatment on the biological tissue materials;
[0146] The surface modification treatment includes oxidation treatment, grafting treatment and reduction treatment performed in sequence;
[0147] The schematic diagram of the surface chemical bond changes of the biological tissue material after the pre-crosslinking treatment S001, oxidation treatment S002, grafting treatment S003, reduction treatment S004 and dislocation crosslinking treatment S005 is shown in FIG. Figure 1 As shown; the storage method specifically includes:
[0148] (1) The biological tissue material was immersed in 0.01% (w / w) sodium dodecyl sulfate at 10°C for 1 h, and then rinsed with PBS buffer; then immersed in 0.5% (w / w) Triton X-100 at 10°C for 2 h, and then rinsed with D-Hanks solution to complete the decellularization process;
[0149] (2) then soaking in a 0.5% (w / w) glutaraldehyde solution at 37° C. for 20 min for pre-crosslinking treatment;
[0150] (3) then immersed in 0.1 mM potassium dichromate at 25°C for 40 min for oxidation treatment;
[0151] (4) then immersed in CB buffer with a concentration of 0.1 M hydroxyethyl methacrylate at 25°C for 24 h for grafting treatment;
[0152] (5) then immersed in PBS buffer with a concentration of 0.1 M sodium cyanoborohydride at 25°C for 24 h for reduction treatment;
[0153] (6) then sequentially performing a first crosslinking and a second crosslinking to perform a staggered crosslinking treatment;
[0154] The first cross-linking comprises: immersing in a mixed solution of a carbonyl activation reagent and a coupling reagent at 25° C. for 8 hours; the concentration of the carbonyl activation reagent in the mixed solution is 40 mM, and the concentration of the coupling reagent is 20 mM; the carbonyl activation reagent is 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride; and the coupling reagent is N-hydroxysuccinimide sulfonic acid sodium salt;
[0155] The second cross-linking comprises: immersing in a metal inhibitor solution having a magnesium concentration of 10 mM at 10° C. for 2 h;
[0156] (7) Finally, the material is extracted three times in a material preservation solution at 25°C, and light induction is performed after each extraction to form three layers of hydrogel coating by a layer-by-layer self-assembly method under ultraviolet light irradiation; the material preservation solution contains 0.02% (w / w) 2-hydroxy-2-methylphenylacetone, 0.05% (w / w) carboxymethyl chitosan (degree of substitution 80%) and 0.08 mM polyhexamethylene biguanide hydrochloride; the immersion time for each extraction is 8 min.
[0157] Example 10
[0158] The present invention provides a storage method for biological tissue materials, the storage method comprising: sequentially performing decellularization treatment, pre-crosslinking treatment, surface modification treatment, dislocation crosslinking treatment and hydrogel coating treatment on the biological tissue materials;
[0159] The surface modification treatment includes oxidation treatment, grafting treatment and reduction treatment performed in sequence;
[0160] The schematic diagram of the surface chemical bond changes of the biological tissue material after the pre-crosslinking treatment S001, oxidation treatment S002, grafting treatment S003, reduction treatment S004 and dislocation crosslinking treatment S005 is shown in FIG. Figure 1 As shown; the storage method specifically includes:
[0161] (1) The biological tissue material was immersed in 0.01% (w / w) sodium dodecyl sulfate at 5°C for 1 h, and then rinsed with PBS buffer; then immersed in 0.5% (w / w) Triton X-100 at 5°C for 4 h, and then rinsed with D-Hanks solution to complete the decellularization process;
[0162] (2) then soaking in a 0.3% (w / w) glutaraldehyde solution at 32° C. for 10 min to perform a pre-crosslinking treatment;
[0163] (3) then immersed in 0.05 mM potassium dichromate at 32°C for 18 min for oxidation treatment;
[0164] (4) then immersed in CB buffer with a concentration of 0.05 M hydroxyethyl methacrylate at 32°C for 24 h for grafting treatment;
[0165] (5) then immersed in PBS buffer with a concentration of 0.05 M sodium cyanoborohydride at 32°C for 18 h for reduction treatment;
[0166] (6) then sequentially performing a first crosslinking and a second crosslinking to perform a staggered crosslinking treatment;
[0167] The first cross-linking comprises: immersing in a mixed solution of a carbonyl activation reagent and a coupling reagent at 32° C. for 4 hours; the concentration of the carbonyl activation reagent in the mixed solution is 20 mM, and the concentration of the coupling reagent is 10 mM; the carbonyl activation reagent is 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride; and the coupling reagent is N-hydroxysuccinimide sulfonic acid sodium salt;
[0168] The second cross-linking comprises: immersing in a metal inhibitor solution having a magnesium concentration of 5 mM at 5° C. for 6 h;
[0169] (7) Finally, the material is extracted 10 times in a material preservation solution at 32°C, and light induction is performed after each extraction to form 10 layers of hydrogel coating by a layer-by-layer self-assembly method through ultraviolet light irradiation; the material preservation solution contains 0.01% (w / w) 2-hydroxy-2-methylphenylacetone, 0.01% (w / w) carboxymethyl chitosan (degree of substitution 80%) and 0.01mM polyhexamethylene biguanide hydrochloride; the immersion time for each extraction is 2 minutes.
[0170] Embodiment 11
[0171] The present invention provides a storage method for biological tissue materials, the storage method comprising: sequentially performing decellularization treatment, pre-crosslinking treatment, surface modification treatment, dislocation crosslinking treatment and hydrogel coating treatment on the biological tissue materials;
[0172] The surface modification treatment includes oxidation treatment, grafting treatment and reduction treatment performed in sequence;
[0173] The schematic diagram of the surface chemical bond changes of the biological tissue material after the pre-crosslinking treatment S001, oxidation treatment S002, grafting treatment S003, reduction treatment S004 and dislocation crosslinking treatment S005 is shown in FIG. Figure 1 As shown; the storage method specifically includes:
[0174] (1) The biological tissue material was immersed in 2% (w / w) sodium dodecyl sulfate at 15°C for 1 h, and then rinsed with D-Hanks solution; then immersed in 2% (w / w) Triton X-100 at 15°C for 1 h, and then rinsed with PBS buffer to complete the decellularization process;
[0175] (2) then immersing in a 0.1% (w / w) glutaraldehyde solution at 25° C. for 60 min for pre-crosslinking treatment;
[0176] (3) then immersed in 0.01 mM potassium dichromate at 37°C for 50 min for oxidation treatment;
[0177] (4) then immersed in CB buffer with a concentration of 0.01 M hydroxyethyl methacrylate at 37°C for 12 h for grafting treatment;
[0178] (5) then immersed in PBS buffer with a concentration of 0.01 M sodium cyanoborohydride at 37°C for 12 h for reduction treatment;
[0179] (6) then sequentially performing a first crosslinking and a second crosslinking to perform a staggered crosslinking treatment;
[0180] The first cross-linking comprises: immersing in a mixed solution of a carbonyl activation reagent and a coupling reagent at 37° C. for 12 hours; the concentration of the carbonyl activation reagent in the mixed solution is 80 mM, and the concentration of the coupling reagent is 40 mM; the carbonyl activation reagent is 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride; and the coupling reagent is sodium salt of N-hydroxysuccinimide sulfonate;
[0181] The second cross-linking comprises: immersing in a metal inhibitor solution having a magnesium concentration of 1 mM at 15° C. for 4 hours;
[0182] (7) Finally, the material is extracted five times in a material preservation solution at 32°C, and light induction is performed after each extraction to form five layers of hydrogel coating by a layer-by-layer self-assembly method through ultraviolet light irradiation; the material preservation solution contains 1% (w / w) 2-hydroxy-2-methylphenylacetone, 0.2% (w / w) carboxymethyl chitosan (degree of substitution 80%) and 0.1 mM polyhexamethylene biguanide hydrochloride; the immersion time for each extraction is 4 min.
[0183] Example 12
[0184] The present invention provides a storage method for biological tissue materials, the storage method comprising: sequentially performing decellularization treatment, pre-crosslinking treatment, surface modification treatment, dislocation crosslinking treatment and hydrogel coating treatment on the biological tissue materials;
[0185] The surface modification treatment includes oxidation treatment, grafting treatment and reduction treatment performed in sequence;
[0186] The schematic diagram of the surface chemical bond changes of the biological tissue material after the pre-crosslinking treatment S001, oxidation treatment S002, grafting treatment S003, reduction treatment S004 and dislocation crosslinking treatment S005 is shown in FIG. Figure 1 As shown; the storage method specifically includes:
[0187] (1) The biological tissue material was immersed in 0.01% (w / w) BSA-14 at 15°C for 1 h, and then rinsed with PBS buffer; then immersed in 1% (w / w) Triton X-100 at 15°C for 2 h, and then rinsed with D-Hanks solution to complete the decellularization process;
[0188] (2) then immersing in a 0.1% (w / w) glutaraldehyde solution at 25° C. for 60 min for pre-crosslinking treatment;
[0189] (3) then immersed in 0.1 mM potassium periodate at 30°C for 30 min for oxidation treatment;
[0190] (4) then immersed in 0.1 M methacrylic anhydride CB buffer at 25°C for 24 h for grafting treatment;
[0191] (5) then immersed in PBS buffer with a concentration of 0.1 M sodium triacetylborohydride at 25°C for 24 h for reduction treatment;
[0192] (6) then sequentially performing a first crosslinking and a second crosslinking to perform a staggered crosslinking treatment;
[0193] The first cross-linking comprises: immersing in a mixed solution of a carbonyl activation reagent and a coupling reagent at 25° C. for 12 hours; the concentration of the carbonyl activation reagent in the mixed solution is 20 mM, and the concentration of the coupling reagent is 10 mM; the carbonyl activation reagent is 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride; and the coupling reagent is 1-hydroxybenzotriazole;
[0194] The second cross-linking comprises: immersing in a metal inhibitor solution with a zinc concentration of 8 mM at 10° C. for 5 h;
[0195] (7) Finally, the material is extracted 10 times in a material preservation solution at 25°C, and light induction is performed after each extraction to form 10 layers of hydrogel coating by a layer-by-layer self-assembly method through ultraviolet light irradiation; the material preservation solution contains 0.01% (w / w) 2-hydroxy-2-methylphenylacetone, 0.1% (w / w) gelatin derivative (Innochem B25612) and 0.1mM polyhexamethylene biguanide hydrochloride; the immersion time for each extraction is 2 minutes.
[0196] Embodiment 13
[0197] The present invention provides a storage method for biological tissue materials, the storage method comprising: sequentially performing decellularization treatment, pre-crosslinking treatment, surface modification treatment, dislocation crosslinking treatment and hydrogel coating treatment on the biological tissue materials;
[0198] The surface modification treatment includes oxidation treatment, grafting treatment and reduction treatment performed in sequence;
[0199] The schematic diagram of the surface chemical bond changes of the biological tissue material after the pre-crosslinking treatment S001, oxidation treatment S002, grafting treatment S003, reduction treatment S004 and dislocation crosslinking treatment S005 is shown in FIG. Figure 1 As shown; the storage method specifically includes:
[0200] (1) The biological tissue material was immersed in 0.01% (w / w) BSA-16 at 15°C for 1 h, and then rinsed with PBS buffer; then immersed in 1% (w / w) Triton X-100 at 15°C for 2 h, and then rinsed with D-Hanks solution to complete the decellularization process;
[0201] (2) then immersing in a 0.2% (w / w) glutaraldehyde solution at 30° C. for 40 min for pre-crosslinking treatment;
[0202] (3) then immersed in 0.1 mM sodium periodate at 28°C for 40 min for oxidation treatment;
[0203] (4) then immersed in 0.1 M methacrylate-containing PBS buffer at 30°C for 12 h for grafting treatment;
[0204] (5) then immersed in PBS buffer with a concentration of 0.05 M sodium borohydride at 30°C for 16 h for reduction treatment;
[0205] (6) then sequentially performing a first crosslinking and a second crosslinking to perform a staggered crosslinking treatment;
[0206] The first cross-linking comprises: immersing in a mixed solution of a carbonyl activation reagent and a coupling reagent at 30° C. for 8 hours; the concentration of the carbonyl activation reagent in the mixed solution is 20 mM, and the concentration of the coupling reagent is 10 mM; the carbonyl activation reagent is 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride; and the coupling reagent is sodium salt of N-hydroxysuccinimide sulfonate;
[0207] The second cross-linking comprises: immersing in a metal inhibitor solution with a zinc concentration of 10 mM at 10° C. for 4 hours;
[0208] (7) Finally, the material is extracted five times in a material preservation solution at 25°C, and light induction is performed after each extraction to form five layers of hydrogel coating by a layer-by-layer self-assembly method under ultraviolet light irradiation; the material preservation solution contains 0.05% (w / w) 2-hydroxy-2-methylphenylacetone, 0.2% (w / w) gelatin derivative (Innochem B25613) and 0.05mM polyhexamethylene biguanide hydrochloride; the immersion time for each extraction is 4 minutes.
[0209] Embodiment 14
[0210] The present invention provides a storage method for biological tissue materials, the storage method comprising: sequentially performing decellularization treatment, pre-crosslinking treatment, surface modification treatment, dislocation crosslinking treatment and hydrogel coating treatment on the biological tissue materials;
[0211] The surface modification treatment includes oxidation treatment, grafting treatment and reduction treatment performed in sequence;
[0212] The schematic diagram of the surface chemical bond changes of the biological tissue material after the pre-crosslinking treatment S001, oxidation treatment S002, grafting treatment S003, reduction treatment S004 and dislocation crosslinking treatment S005 is shown in FIG. Figure 1 As shown; the storage method specifically includes:
[0213] (1) The biological tissue material was immersed in 0.01% (w / w) hexadecyl ammonium bromide at 10°C for 1 h, and then rinsed with PBS buffer; then immersed in 1% (w / w) BSA-16 at 10°C for 2 h, and then rinsed with D-Hanks solution to complete the decellularization process;
[0214] (2) then immersing in a 0.3% (w / w) glutaraldehyde solution at 25° C. for 50 min for pre-crosslinking treatment;
[0215] (3) then immersing in 0.05 mM 2,2,6,6-tetramethylpiperidinyl oxide at 25° C. for 20 min for oxidation treatment;
[0216] (4) then immersed in a 0.1 M acryloyl chloride solution in dimethyl sulfoxide at 25°C for 4 h for grafting treatment;
[0217] (5) then immersed in PBS buffer with a concentration of 0.1 M sodium borohydride at 25°C for 16 h for reduction treatment;
[0218] (6) then sequentially performing a first crosslinking and a second crosslinking to perform a staggered crosslinking treatment;
[0219] The first cross-linking comprises: immersing in a mixed solution of a carbonyl activation reagent and a coupling reagent at 25° C. for 4 hours; the concentration of the carbonyl activation reagent in the mixed solution is 40 mM, and the concentration of the coupling reagent is 20 mM; the carbonyl activation reagent is 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride; and the coupling reagent is 1-hydroxybenzotriazole;
[0220] The second cross-linking comprises: immersing in a metal inhibitor solution with a zinc concentration of 5 mM at 10° C. for 6 hours;
[0221] (7) Finally, the material is extracted eight times in a material preservation solution at 25° C., and light induction is performed after each extraction to form eight layers of hydrogel coating by a layer-by-layer self-assembly method through ultraviolet light irradiation; the material preservation solution contains 0.01% (w / w) 2-hydroxy-2-methylphenylacetone, 0.05% (w / w) sodium alginate (Innochem A21509) and 0.01 mM polyhexamethylene biguanide hydrochloride; the immersion time for each extraction is 2 min.
[0222] Embodiment 15
[0223] The present invention provides a storage method for biological tissue materials, the storage method comprising: sequentially performing decellularization treatment, pre-crosslinking treatment, surface modification treatment, dislocation crosslinking treatment and hydrogel coating treatment on the biological tissue materials;
[0224] The surface modification treatment includes oxidation treatment, grafting treatment and reduction treatment performed in sequence;
[0225] The schematic diagram of the surface chemical bond changes of the biological tissue material after the pre-crosslinking treatment S001, oxidation treatment S002, grafting treatment S003, reduction treatment S004 and dislocation crosslinking treatment S005 is shown in FIG. Figure 1 As shown; the storage method specifically includes:
[0226] (1) The biological tissue material was immersed in 0.1% (w / w) BSA-16 at 15°C for 1 h, and then rinsed with PBS buffer; then immersed in 1% (w / w) Triton X-100 at 15°C for 2 h, and then rinsed with D-Hanks solution to complete the decellularization process;
[0227] (2) then immersing in a 0.1% (w / w) glutaraldehyde solution at 30° C. for 50 min to perform a pre-crosslinking treatment;
[0228] (3) then immersed in 0.1 mM sodium periodate at 25°C for 40 min for oxidation treatment;
[0229] (4) then immersed in 0.1 M methacrylic anhydride CB buffer at 25 °C for 12 h for grafting treatment;
[0230] (5) then immersed in CB buffer with a concentration of 0.1 M sodium borohydride at 25°C for 16 h for reduction treatment;
[0231] (6) then sequentially performing a first crosslinking and a second crosslinking to perform a staggered crosslinking treatment;
[0232] The first cross-linking comprises: immersing in a mixed solution of a carbonyl activation reagent and a coupling reagent at 25° C. for 12 hours; the concentration of the carbonyl activation reagent in the mixed solution is 20 mM, and the concentration of the coupling reagent is 10 mM; the carbonyl activation reagent is 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride; and the coupling reagent is 1-hydroxybenzotriazole;
[0233] The second cross-linking comprises: immersing in a metal inhibitor solution with a zinc concentration of 10 mM at 10° C. for 4 hours;
[0234] (7) Finally, the material was extracted 10 times in a material preservation solution at 25°C, and light induction was performed after each extraction to form 10 layers of hydrogel coating by a layer-by-layer self-assembly method through ultraviolet light irradiation; the material preservation solution contained 0.01% (w / w) 2-hydroxy-2-methylphenylacetone, 0.05% (w / w) soluble cellulose (thermo scientific 045847) and 0.1 mM polyhexamethylene biguanide hydrochloride; the immersion time for each extraction was 3 min.
[0235] Comparative Example 1
[0236] This comparative example provides a storage method for biological tissue materials, and the storage method comprises: directly preserving the biological tissue materials with glutaraldehyde.
[0237] Performance Characterization
[0238] (1) Tissue rehydration performance test
[0239] The 10×10 mm sample was spread on a smooth stainless steel plate and placed in a constant temperature and humidity chamber at 40°C and 70% relative humidity for one week. The sample was then immersed in PBS buffer and the rehydration of the sample was observed. The results are shown in Table 1.
[0240] Among them, the control group was preserved in a natural dry state, and its rehydration schematic diagram is shown in Figure 5; Figure 5-1 It is a dry tissue placed in a constant temperature and humidity chamber at 40°C and 70% relative humidity for one week; Figure 5-2 Schematic diagram of rehydration after incubation in physiological saline at 37°C for 30 minutes.
[0241] Among them, the coating formed on the surface of the biological tissue material in Examples 1 to 5 has only van der Waals forces. Specifically, the schematic diagram of the rehydration of the biological tissue material obtained after treatment in Example 5 is shown in FIG2 ; wherein, Figure 2-1 The sample is a dry tissue placed in a constant temperature and humidity chamber at 40°C and 70% relative humidity for one week; Figure 2-2 The diagram is a rehydration diagram of incubating in physiological saline at 37°C for 15 minutes; Figure 2-3 Schematic diagram of rehydration after incubation in physiological saline at 37°C for 30 minutes.
[0242] Depend on Figure 2-1 to Figure 2-3 It can be seen that the van der Waals force between biological tissue and coating is not sufficient to maintain the long-term stability of the coating, which is not conducive to the preservation of pericardium. This is also one of the reasons that cause the rehydration curling of biological tissue.
[0243] The coatings formed on the surface of the biological tissue material in Examples 6 to 15 have the synergistic effect of van der Waals forces and covalent bonds. Specifically, the schematic diagram of the rehydration of the biological tissue material obtained after treatment in Example 7 is shown in FIG3 ; wherein, Figure 3-1 The sample is a dry tissue placed in a constant temperature and humidity chamber at 40°C and 70% relative humidity for one week; Figure 3-2 The diagram is a rehydration diagram of incubating in physiological saline at 37°C for 15 minutes; Figure 3-3 Schematic diagram of rehydration after incubation in physiological saline at 37°C for 30 minutes.
[0244] The schematic diagram of the rehydration of the biological tissue material obtained after treatment in Example 12 is shown in FIG4 ; wherein, Figure 4-1 The sample is a dry tissue placed in a constant temperature and humidity chamber at 40°C and 70% relative humidity for one week; Figure 4-2The diagram is a rehydration diagram of incubating in physiological saline at 37°C for 15 minutes; Figure 4-3 Schematic diagram of rehydration after incubation in physiological saline at 37°C for 30 minutes.
[0245] Depend on Figure 3-1 to Figure 3-3 ,as well as Figure 4-1 to Figure 4-3 It can be seen that the biological tissue treated by the relevant technical solutions flattens from a dry state to a wet state quickly, the corresponding solution of Example 7 has a slight curling after rehydration, and the corresponding solution of Example 12 flattens smoothly and has good flexibility.
[0246] Table 1
[0247]
[0248]
[0249] (2) Antibacterial performance test
[0250] 500 mg of the sample cut into small pieces was placed in 10 mL of 5×10 5 CFU / mL of bacterial suspension in a conical flask; shake the flask at 37°C (120 rpm). After incubation for 0 hours and 4 hours, 20 μL of bacterial suspension was spread on a nutrient agar plate; colony forming units were counted after culturing at 37°C for 18 hours. The smaller the number of colonies, the better the antibacterial effect. The results are shown in Table 2.
[0251] The number of colonies after 0 hours of incubation is M0, and the number of colonies after 4 hours of incubation is M1. The inhibition rate is:
[0252] Antibacterial rate = [(M0-M1) / M0] × 100%;
[0253] (3) Enzymatic stability test
[0254] Collagen and elastin stability of cross-linked tissues was measured by percentage weight loss after collagenase II and elastase treatment: Samples (1 × 1 cm 2 , n = 6 per group) were freeze-dried and weighed (W0); the dried fragments were mixed with 125 U mL -1 Collagenase II in Tris buffer (Tris 0.1 M, CaCl2 0.05 M, pH 7.4) or containing 30 U mL -1 The elastase was incubated in Tris buffer (Tris 0.1 M, CaCl2 0.001 M, pH 7.8) for 24 hours; the enzyme-treated tissue was rinsed three times with distilled water, then freeze-dried and weighed (Wt). The results are shown in Table 2.
[0255] Table 2
[0256]
[0257] As shown in Table 2, comparative example 1 uses glutaraldehyde for antibacterial preservation, and the antibacterial property of pericardial tissue comes from a trace amount of free glutaraldehyde, which has no obvious antibacterial effect. From the results of the antibacterial rate, it can be seen that the antibacterial rate of comparative example 1 is significantly lower than that of the test groups of other embodiments.
[0258] Examples 1 to 3 use layer-by-layer self-assembly to form a hydrogel coating, which has a certain antibacterial effect compared to Comparative Example 1. The force of the hydrogel coating is van der Waals force, and no chemical bond is formed. Its antibacterial stability is lower than that of Example 6, which is chemically grafted, and its antibacterial performance is lower.
[0259] Example 4 was subjected to oxidation treatment, and its calcium content was significantly reduced, indicating that oxidation treatment can reduce glutaraldehyde residues and enhance stability.
[0260] Example 5 carried out reduction treatment to improve the instability factor caused by glutaraldehyde cross-linking fixation.
[0261] Example 6 was grafted, and compared with Example 1, the chemical bonding force between the hydrogel coatings was increased, the coating stability was increased, the effective antibacterial components were retained, and the antibacterial performance was greatly improved. The calcium content in Example 6 was reduced, indicating that grafting can improve the anti-calcification performance, and the retention amount of the antibacterial agent can achieve a long-term antibacterial effect.
[0262] Example 7 was pre-crosslinked, which increased the stability of the composite cross-linked reinforced fiber and improved its anti-calcification performance compared to Example 1.
[0263] Example 8 was decellularized, which can increase tissue biocompatibility, improve biocompatibility, reduce immune rejection caused by foreign matter, increase anti-calcification function, and also have benefits for increasing anti-calcification performance.
[0264] Based on decellularization, pretreatment, surface modification and composite cross-linking, Examples 9-15 improve the performance of the tissue by adjusting the extraction and light cross-linking time. Comprehensively evaluated from the perspectives of anti-calcification, anti-enzymatic hydrolysis, and antibacterial rate, Examples 9-15 all have excellent anti-calcification, anti-enzymatic hydrolysis, biocompatibility, and good antibacterial performance. The introduction of composite cross-linking significantly improves the anti-enzymatic hydrolysis performance.
[0265] In summary, the present invention performs hydrogel coating treatment on biological tissue materials to form a hydrogel coating that prevents direct contact between biological tissue and glutaraldehyde, effectively avoiding the problems of aldehyde residue and calcification caused by storage in glutaraldehyde solution; moreover, the storage method provided by the present invention does not require dehydration treatment, and can avoid the problems of too low water content in dry-preserved biological tissue materials, resulting in storage performance attenuation and difficulty in rehydration; in addition, the hydrogel coating formed by the hydrogel coating treatment can also make the surface of the biological tissue material have a water-retaining effect, thereby improving the storage stability.
[0266] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for storing biological tissue materials, characterized in that: The storage method comprises: The biological tissue material is subjected to hydrogel coating treatment to form a hydrogel coating by layer-by-layer self-assembly.
2. The storage method according to claim 1, characterized in that: The hydrogel coating treatment comprises: extracting the biological tissue material in a material preservation solution at least once, and performing light induction at least once each time of extraction to form a hydrogel coating that protects the biological tissue material; Preferably, the soaking time of each extraction is 2-8 minutes; Preferably, the number of layers of the hydrogel coating formed by layer-by-layer self-assembly is 3-10; Preferably, the material preservation solution contains 0.01-1% (w / w) of a photoinitiator and 0.01-0.2% (w / w) of a double-bond modified polymer material; Preferably, the photoinitiator comprises an ultraviolet photoinitiator; Preferably, the ultraviolet light initiator includes any one of 2-hydroxy-2-methylphenylpropanone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylphenylpropanone, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone or 2-hydroxy-2-methyl-1-[4-(tert-butyl)phenyl]-1-propanone, or a combination of at least two thereof; Preferably, the double-bond modified polymer material comprises any one of chitosan, chitosan derivatives, gelatin, gelatin derivatives, soluble cellulose, soluble cellulose derivatives, sodium alginate, sodium alginate derivatives, hyaluronic acid, hyaluronic acid derivatives, chondroitin sulfate, chondroitin sulfate derivatives, silk protein, silk protein derivatives, β-cyclodextrin or β-cyclodextrin derivatives, or a combination of at least two thereof; preferably chitosan and / or chitosan derivatives; Preferably, the material preservation solution also contains 0.01-1 mM of antibacterial active substances; Preferably, the antibacterial active substance includes any one or a combination of at least two of biguanide substances, isothiazole substances, phenol ether substances or phenol substances; Preferably, the temperature of the hydrogel coating treatment is 25-37°C.
3. The storage method according to claim 1 or 2, characterized in that: The biological tissue material includes any one of pericardial tissue, cartilage tissue or skin tissue; Preferably, the biological tissue material is subjected to surface treatment before being subjected to the hydrogel coating treatment; Preferably, the surface treatment includes any one or a combination of at least two of pre-crosslinking treatment, surface modification treatment or dislocation crosslinking treatment; Preferably, the surface modification treatment includes any one of oxidation treatment, grafting treatment or reduction treatment, or a combination of at least two of them.
4. The storage method according to claim 3, characterized in that: The pre-crosslinking treatment comprises: soaking in a glutaraldehyde solution; Preferably, the concentration of the glutaraldehyde solution is 0.1-0.5% (w / w); Preferably, the pre-crosslinking treatment is carried out at a temperature of 25-37° C. and for a time of 10-60 min.
5. The storage method according to claim 3 or 4, characterized in that: The oxidation treatment comprises: immersing in an oxidant solution; Preferably, the concentration of the oxidant solution is 0.01-0.1 mM; Preferably, the oxidant in the oxidant solution comprises any one or a combination of at least two of sodium periodate, potassium periodate, potassium dichromate, peracetic acid, hydrogen peroxide or 2,2,6,6-tetramethylpiperidinyl oxide; Preferably, the oxidation treatment is carried out at a temperature of 25-37°C and for a time of 10-50 minutes.
6. The storage method according to any one of claims 3 to 5, characterized in that: The grafting treatment comprises: soaking in a solution containing a terminal active double bond structure substance; Preferably, the concentration of the solution containing the terminal active double bond structure substance is 0.01-0.1M; Preferably, the terminal active double bond structure-containing substance comprises any one or a combination of at least two of methacrylic anhydride, methacrylic anhydride oil, di(2-methyl-2-acrylate) 2-hydroxy-1,3-propylene glycol ester, hydroxyethyl methacrylate or acryloyl chloride; Preferably, the grafting treatment is carried out at a temperature of 25-37° C. and for a time of 12-24 hours.
7. The storage method according to any one of claims 3 to 6, characterized in that: The reduction treatment comprises: immersing in a reducing agent solution; Preferably, the concentration of the reducing agent solution is 0.01-0.1M; Preferably, the reducing agent in the reducing agent solution includes any one of sodium borohydride, sodium cyanoborohydride or sodium triacetylborohydride, or a combination of at least two thereof; Preferably, the reduction treatment is carried out at a temperature of 25-37° C. and for a time of 12-24 h.
8. The storage method according to any one of claims 3 to 7, characterized in that: The dislocation cross-linking treatment includes a first cross-linking and a second cross-linking performed sequentially; Preferably, the first cross-linking comprises: soaking in a mixed solution of a carbonyl activation reagent and a coupling reagent; Preferably, the concentration of the carbonyl activation reagent in the mixed solution is 20-80 mM, and the concentration of the coupling reagent is 10-40 mM; Preferably, the carbonyl activation reagent comprises any one or a combination of at least two of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride or dimethylaminopropylethylcarbodiimide; Preferably, the coupling reagent comprises any one or a combination of at least two of N-hydroxysuccinimide sulfonic acid sodium salt, 1-hydroxybenzotriazole or benzyloxycarbonyl succinimide; Preferably, the temperature of the first cross-linking is 25-37°C and the time is 4-12h; Preferably, the second cross-linking comprises: soaking in a metal inhibitor solution; Preferably, the metal ion concentration in the metal inhibitor solution is 1-10 mM; Preferably, the metal ions in the metal inhibitor solution include any one of iron ions, zinc ions or magnesium ions, or a combination of at least two thereof; Preferably, the temperature of the second cross-linking is 5-15° C. and the time is 2-6 hours.
9. The storage method according to any one of claims 3 to 8, characterized in that: The storage method further comprises a decellularization treatment prior to the surface treatment; Preferably, the decellularization treatment comprises: soaking in a detergent solution; Preferably, the temperature of the decellularization treatment is 5-15°C and the time is 1-4h; Preferably, the concentration of the detergent solution is 0.01-2% (w / w); Preferably, the detergent in the detergent solution includes any one of sodium dodecyl sulfate, hexadecyl ammonium bromide, betaine-type detergent or Triton X-100, or a combination of at least two thereof; Preferably, the betaine-type detergent comprises 3-[N,N-dimethyldimethyl(3-myristoylamidepropyl)ammonium]propane-1-sulfonate and / or 3-[N,N-dimethyl(3-palmitamidopropyl)ammonium]-propanesulfonic acid inner salt.
10. The storage method according to any one of claims 1 to 9, characterized in that: The storage method comprises the following steps: (1) The biological tissue material is immersed in a detergent solution with a concentration of 0.01-2% (w / w) at 5-15° C. for 1-4 hours to perform a decellularization treatment; the detergent in the detergent solution includes any one of sodium dodecyl sulfate, hexadecyl ammonium bromide, betaine-type detergent or Triton X-100, or a combination of at least two thereof; (2) then immersing in a 0.1-0.5% (w / w) glutaraldehyde solution at 25-37° C. for 10-60 min to perform a pre-crosslinking treatment; (3) then immersing in an oxidant solution with a concentration of 0.01-0.1 mM at 25-37° C. for 10-50 min for oxidation treatment; the oxidant in the oxidant solution comprises any one of sodium periodate, potassium periodate, potassium dichromate, peracetic acid, hydrogen peroxide or 2,2,6,6-tetramethylpiperidinyl oxide, or a combination of at least two thereof; (4) then immersing in a solution containing a terminal active double bond structure substance at a concentration of 0.01-0.1 M at 25-37° C. for 12-24 hours for grafting treatment; the terminal active double bond structure substance comprises any one of methacrylic anhydride, methacrylic anhydride oil, di(2-methyl-2-acrylate) 2-hydroxy-1,3-propylene glycol ester, hydroxyethyl methacrylate or acryloyl chloride, or a combination of at least two thereof; (5) then immersing in a reducing agent solution with a concentration of 0.01-0.1 M at 25-37° C. for 12-24 hours for reduction treatment; the reducing agent in the reducing agent solution includes any one of sodium borohydride, sodium cyanoborohydride or sodium triacetylborohydride, or a combination of at least two thereof; (6) then sequentially performing a first crosslinking and a second crosslinking to perform a staggered crosslinking treatment; The first cross-linking comprises: immersing in a mixed solution of a carbonyl activation reagent and a coupling reagent at 25-37° C. for 4-12 hours; the concentration of the carbonyl activation reagent in the mixed solution is 20-80 mM, and the concentration of the coupling reagent is 10-40 mM; The second cross-linking comprises: immersing in a metal inhibitor solution having a metal ion concentration of 1-10 mM at 5-15° C.; the metal ions in the metal inhibitor solution comprise any one of iron ions, zinc ions or magnesium ions or a combination of at least two thereof; (7) Finally, the material is extracted at least once in a material preservation solution at 25-37°C, and light induction is performed at least once each time the extraction is performed to form 3-10 layers of hydrogel coatings to protect the biological tissue material; the material preservation solution contains 0.01-1% (w / w) of a photoinitiator, 0.01-0.2% (w / w) of a double-bond modified polymer material, and 0.01-1 mM of an antibacterial active substance.
Citation Information
Patent Citations
Method for preserving artificial biological tissue
CN109430244A
Method of artificial biological valve
CN109833519A
Preparation method of swimming bladder bioprosthetic valve material and preservation method thereof
CN110755688A
Treatment method of artificial biological valve
CN113476659A
Tissue-engineered bone constructed based on hydrogel material as well as preparation method and application of tissue-engineered bone
CN115475283A